In Vivo Study of CORAGRAF: A Preliminary Results. - Rosdan, S; Al-Salihi, K A; Suzina, A H; Samsudin, A R (Malaysian Medical Association, 2004)
Natural coral is a bone graft substitute, which has been widely used' in maxillofacial, orthopaedic, ORL and periodontal surgery.